The Effectiveness of Learning Media with Virtual Reality Non Immersive Ventilator Laboratory (Ventlab VR) on Student Knowledge, Learning Motivation, and Self-Efficacy - Yohanes Wahyu Nugroho; Yeni Nur Rahmayanti; Desiyani Nani; Arif Setyo Upoyo (Lembaga Publikasi Ilmiah Nusantara, 2026)
Mechanical ventilators are complex medical devices essential to critical nursing education; however, learning in health colleges has predominantly been conducted through conventional methods such as lectures and handbooks, with limited practical exposure. Limited equipment, high costs, and lack of hands-on experience have contributed to low levels of knowledge, learning motivation, and self-efficacy among students. This study was conducted to develop and evaluate a Virtual Reality-based Ventilator Laboratory using 360-degree video as an innovative learning medium that provides immersive and interactive experiences. The research applied a Research and Development approach using the Analysis, Design, Development, Implementation, and Evaluation model. The effectiveness evaluation employed a quasi-experimental design with a pretest–posttest control group. A total of 50 nursing students were randomly assigned to an intervention group and a control group. Data were collected using validated questionnaires and analyzed using paired and independent-samples t-tests and effect-size analysis. The results showed significant improvements in knowledge, learning motivation, and self-efficacy in the intervention group compared to the control group. The intervention demonstrated a moderate effect on knowledge and large effects on learning motivation and self-efficacy. It was concluded that Virtual Reality-based learning media were effective in enhancing students' understanding of mechanical ventilators.